Congenital Amyelinating Neuropathy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
A case of severe neurogenic arthrogryposis multiplex congenita caused by absence of peripheral nerve myelin in an infant who died at age 31 days of aspiration pneumonia is described from the Dept of Neurology, Neuromuscular Division, Johns Hopkins University School of Medicine, Baltimore, MD.